Change and Its Repercussions for the Banking Industry - Ichak Kalderon Adizes (Journal of Central Banking Theory and Practice, 2014)
Changes have always existed but their speed and frequency have become rather apparent. Changes are present in all areas of life, but here we focus on those happening in the banking industry. Banks are undergoing revolutionary changes and they must change or perish in their present form. The article explains why banks must change and what are the threats to both asset and liability sides they would face otherwise. Changes result in modifications of strategies, organizations and management. The article concludes that banks that are the most flexible and able to adapt will win the day.
Keywords: G21; G34; 330; Change; banking system; strategy; profitability